For which option is credit risk more representative on China banks' total factor productivity: efficiency change or technological progress? - Sufian, Fadzlan (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to provide new empirical evidence on the impact of credit risk on China banks’ total factor productivity.